Combining phages and antibiotic to enhance antibiofilm efficacy against an in vitro dual species wound biofilm - Ergun Akturk; Luís D.R. Melo; Hugo Oliveira; Aurélie Crabbé; Tom Coenye; Joana Azeredo (Biofilm, 2023)
Chronic wound management is extremely challenging because of the persistence of biofilm-forming pathogens, such as Pseudomonas aeruginosa and Staphylococcus aureus, which are the prevailing bacterial species that co-infect chronic wounds. Phage therapy has gained an increased interest to treat biofilm-associated infections, namely when combined with antibiotics. Here, we tested the effect of gentamicin as a co-adjuvant of phages in a dual species-biofilm wound model formed on artificial dermis. The biofilm-killing capacity of the tested treatments was significantly increased when phages were combined with gentamicin and applied multiple times as multiple dose (three doses, every 8 h). Our results suggest that gentamycin is an effective adjuvant of phage therapy particularly when applied simultaneously with phages and in three consecutive doses. The multiple and simultaneous dose treatment seems to be essential to avoid bacterial resistance development to each of the antimicrobial agents.